PENGARUH PENEMPATAN KERJA DAN MUTASI TERHADAP KINERJA PEGAWAI RUMAH SAKIT UNIVERSITAS ANDALAS PADANG - Khairiyyah, Yaumil; Febriani, Febriani; Yanti, Budi (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2020)
Abstract: This study aims to determine the effect of work placement and mutation on the performance of Andalas University Hospital Padang staff. The research method used is quantitative. The sampling technique used was saturated sampling, so the sample in the study was 139 respondents. Data analysis techniques used are multiple linear regression, t test, F test and coefficient of determination. The level of performance provided by employees to the Andalas University Hospital in the form of growth and development of the Andalas University Hospital from year to year shows good performance in terms of the building and spatial planning and the addition of patient beds. Along with the addition of supporting facilities and services must be balanced with the provision of competent Human Resources (HR) through job placement and mutations given to employees. Based on multiple linear regression analysis found that Y = 15,424 + 0,391 X1 + 0,600 X2 + e. Based on the results of research on work placement and mutation partially positive and significant effect on the performance of Andalas University Hospital Padang staff. Based on the simultaneous test results it is known that work placement and mutation together have a significant effect on the performance of Andalas University Hospital Padang employees, while the coefficient of determination results obtained Adjusted RSquare of 29%. Keywords: Job Placement, Mutation and Employee Performance